1999
DOI: 10.1111/j.1875-595x.1999.tb00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion and orthodontic treatment need of secondary school students in Nigeria according to the dental aesthetic index (DAI)

Abstract: The aims of this study were to measure the distribution, prevalence and the severity of malocclusion and treatment need amongst randomly selected (n = 703) rural and urban Nigerian children aged 12-18 years (mean 14.0 +/- 1.84) using the dental aesthetic index (DAI), and to assess whether malocclusion was affected by age, gender and socio-economic background. Data were collected according to the method recommended by WHO. Most of the children (77.4 per cent) had a dental appearance which required no orthodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
56
10
16

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 14 publications
22
56
10
16
Order By: Relevance
“…The Dental Aesthetic Index (DAI) satisfies this need as well as being a simple and universally acceptable index, which can be used in epidemiological surveys to assess unmet treatment need 15 . There are several reports on occlusion and malocclusion among Nigerian children which had focused on the normal population [16][17][18][19][20][21][22] . However, there are relatively few studies on the handicapped in Nigeria especially in relation to orthodontics 13,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…The Dental Aesthetic Index (DAI) satisfies this need as well as being a simple and universally acceptable index, which can be used in epidemiological surveys to assess unmet treatment need 15 . There are several reports on occlusion and malocclusion among Nigerian children which had focused on the normal population [16][17][18][19][20][21][22] . However, there are relatively few studies on the handicapped in Nigeria especially in relation to orthodontics 13,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies that adopted the DAI index in the investigation of malocclusion found that approximately 10.0% of individuals were evaluated in the incapacitating category 10,16,22 , with the most significant value being related in Toronto, where 42.6% of the sample were found to have this degree of malocclusion 8 . Locker et al 8 justified this by bearing in mind that his was a convenience sample, using orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to orthodontic treatment needs, the MSI presented a statistically different proportion The epidemiologic instruments adopted by researchers in their investigations has been rather varied. The IOTN and DAI were the most frequently adopted indices [4][5]8,[10][11][13][14][16][17][18][19][20]22 , while some studies were based on the evaluation of a specific occlusal alteration [2][3]6,9,12,21,23 . The amplitude of occlusion conditions, allied to the diverse methods of measuring malocclusions has made it difficult to perform comparisons of the results of epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations